ECONOMIC ASPECTS OF THE US DE JURE RECOGNITION OF THE BALTIC STATES IN 1922 - Medijainen, Eero (Baltic Journal of Political Science, 2012)
A certain unity among the Baltic states emerged during their simultaneous fights for independence and for recognition by the great powers in Europe and the US. The recognition was given separately to Estonia, Latvia, and Lithuania, and not commonly to the Baltic states. This article tries to determine when and under what circumstances the Baltic question reached the institutions and leading persons dealing with foreign relations in the US as a separate problem independent of Russia. After the independence of the Baltic states, there followed a repelling attitude from the US and non-recognition until 1922.